2009
DOI: 10.28945/3389
|View full text |Cite
|
Sign up to set email alerts
|

M-Government Services Initiatives in Oman

Abstract: Information technology and communications have now become the main elements that move forward and help Oman in its national development process. Internet penetration in most developing countries like Oman is still low as oppose to mobiles dissemination, despite the government plans and strategies to enhance internet diffusion. Internet subscribers comprised about 2.5% of the general population of Oman. In contrast, the number of mobile holders increased substantially since the launch of these services in 1996.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…A distinguishing feature of the country is its young population (ages 15 and under) which currently accounts for 50% of the total population. (Naqvi and Al-Shihi, 2009). This rise is a reflection of "the pace of progress through initiatives to build of ICT infrastructure, over electronic services and build capacity within the country to harness the power of technology" (Information Technology Authority, 2009).…”
Section: Background On Omanmentioning
confidence: 99%
“…A distinguishing feature of the country is its young population (ages 15 and under) which currently accounts for 50% of the total population. (Naqvi and Al-Shihi, 2009). This rise is a reflection of "the pace of progress through initiatives to build of ICT infrastructure, over electronic services and build capacity within the country to harness the power of technology" (Information Technology Authority, 2009).…”
Section: Background On Omanmentioning
confidence: 99%
“…This service mode and pattern change inevitably necessitates changes in the behavioral, psychological, and social characteristics that make up citizen attitudes which lead to intention. As a result, the success of this new trend of transformational government initiated through mGov depends entirely on the attitudinal accommodation of citizens to the new phenomena of mGov (Misuraca, 2009;Naqvi and Al-Shihi, 2009;Trimi and Sheng, 2008). Thus, identifying and formulating the sources of beliefs of the development of an attitude leading to intention toward mGov is a vital concern for successful development and implementation of a well-structured mGov system, and it, consequently, was set as the first objective of this research.…”
Section: Introductionmentioning
confidence: 99%
“…A recent estimate indicated that over half of the Omani population has mobile devices, while the mobile infrastructure in Oman is currently covering 95% of the country (Ministry of National Economy 2007). (Naqvi and Al-Shihi, 2009). This rise is a clear indication of the progress made.…”
Section: Communications Of the Ibimamentioning
confidence: 99%